Assessing Nurses' Readiness for Bedside Medication Administration Technology - Ibrahim Saudi Ibrahim Alotaibi, Marzouq Mohammed Alshabawi, Musab Abdullah Hamian Alotaibi, Faiz Faid Mohammed Alenazi, Rashed Sager Alharbi, Hamad Mufarreh Alqahtani, Faisal Ben Shaya Alotaibi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The ongoing concern regarding medication errors in hospitals has prompted the recommendation for the implementation of Information Technology (IT) in medication administration processes. This IT initiative aims to support nurses in administering medications safely, reduce the occurrence of medication errors, and enhance overall patient safety. Its imminent introduction in several hospitals underscores the importance of assessing nurses' readiness and acceptance of such technology, crucial for its successful adoption. This descriptive study utilized the Technology Acceptance Model to gauge nurses' preparedness for using IT in medication administration . The study involved nurses from three major hospitals in Beirut, gathering data on their demographics, attitudes, and perceptions of IT's usefulness and ease of use in medication administration. ,nurses voluntarily completing the questionnaire either manually or electronically. The findings revealed a correlation between nurses' attitudes towards the proposed IT system and their perceptions of its usefulness and ease of use. While a majority displayed a positive inclination towards the system and scored high on these perceptions, approximately 20% of nurses exhibited a negative attitude towards its adoption.